1990
DOI: 10.1021/bi00486a022
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation in short-chain lecithin/gel-state long chain lecithin aggregates

Abstract: Small bilayer particles form spontaneously from gel-state long-chain phospholipids such as dipalmitoylphosphatidylcholine and 0.2 mol fraction short-chain lecithins (e.g., diheptanoyl-phosphatidylcholine). When the particles are incubated at temperatures greater than the Tm of the long-chain phosphatidylcholine (PC), the particles rapidly fuse (from 90-A to greater than or equal to 5000-A radius); this transition is reversible. A possible explanation for this behavior involves patching or phase separation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…At T c , the interactions of short-chain phosphatidylcholine (dihexanoyl or diheptanoyl) with long-chain (dimyristoyl, dipalmitoyl, or distearoyl) phosphatidylcholine would predominantly have characteristics of the long-chained component. [23,24] Thus, mixtures of DHPC and DMPC in water would be expected to form discoidal aggregates in which a flat DMPC bilayer is stabilized by the DHPC rim. [25] Using solid-state 31 P NMR spectrometry, we confirmed that the surfaces of bicelles orient parallel to the magnetic field (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…At T c , the interactions of short-chain phosphatidylcholine (dihexanoyl or diheptanoyl) with long-chain (dimyristoyl, dipalmitoyl, or distearoyl) phosphatidylcholine would predominantly have characteristics of the long-chained component. [23,24] Thus, mixtures of DHPC and DMPC in water would be expected to form discoidal aggregates in which a flat DMPC bilayer is stabilized by the DHPC rim. [25] Using solid-state 31 P NMR spectrometry, we confirmed that the surfaces of bicelles orient parallel to the magnetic field (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Since various assemblies are expected, depending on the states of DMPC vesicle membrane (gel and liquid crystalline) and on the DHPC concentrations, in the present system, the tran- sition process may be more complicated than that explained by three-stage model [20][21][22][23]. It is demonstrated that the vesicle to micelle transition takes place through the formation of thread-like intermediate structure under the experimental condition of this study, and the possible mechanism of the transition process will be discussed.…”
Section: Introductionmentioning
confidence: 94%
“…[27][28][29][30][31]35 The typical bicelle diameter was around 20 nm with a bilayer thickness of about 6 nm at room temperature. The disc-like bicelles were formed by mixing the zwitterionic long-chain lipid 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) and the short-chain lipid 1,2-diheptanoylsn-glycero-3-phosphocholine (diC7PC) in aqueous solution.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%